(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This scientific article examines the technologies for using environmentally safe fuels and lubricants in automobile transport. The study analyzes the types of eco-friendly fuels, such as biofuels, compressed natural gas (CNG), liquefied petroleum gas (LPG), and synthetic lubricants, as well as their impact on reducing harmful emissions, improving engine efficiency, and extending the service life of vehicles. The article also discusses fuel-saving and digital monitoring technologies that optimize fuel and lubricant consumption. The research highlights the practical significance of implementing environmentally safe fuels and lubricants to ensure sustainable transport, reduce environmental pollution, and increase economic efficiency in the automotive sector.